2016
DOI: 10.1111/jnu.12265
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian Nursing Work Environments, Intent to Stay, and Job Satisfaction

Abstract: Purpose: The purpose of this study was to examine associations among the nursing work environment, nurse job satisfaction, and intent to stay for nurses who practice in hospitals in Jordan. Design: A quantitative descriptive cross-sectional survey design was used. Methods: Data were collected through survey questionnaires distributed to 650 registered nurses (RNs) who worked in three hospitals in Jordan. The selfreport questionnaire consisted of three instruments and demographic questions. The instruments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
124
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 24 publications
15
124
2
6
Order By: Relevance
“…Many studies were congruent with these findings, while others were not. For example, a previous study revealed that Jordanian nurses who work for the public sector in the governmental hospitals showed higher intent to stay rates than those work for private or university hospitals which was congruent with our findings (Al‐Hamdan, Manojlovich, & Tanima, ). In addition, similar to our findings, Mrayyan () revealed that married nurses and those older than 30 years had higher rates of retention and stay in their jobs.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies were congruent with these findings, while others were not. For example, a previous study revealed that Jordanian nurses who work for the public sector in the governmental hospitals showed higher intent to stay rates than those work for private or university hospitals which was congruent with our findings (Al‐Hamdan, Manojlovich, & Tanima, ). In addition, similar to our findings, Mrayyan () revealed that married nurses and those older than 30 years had higher rates of retention and stay in their jobs.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise in Saudi Arabia, Aboshaiqah () found dimensions of NWE such as safe staffing, authentic leadership and teamworking were perceived positively by nurses. In Jordan, Al‐Hamdan et al () found working in positive NWE is associated with more NJS and intent to retain work.…”
Section: Introductionmentioning
confidence: 99%
“…The role of nurses in healthcare delivery is important given that they are at the forefront of patient care and constitute the largest group of healthcare providers (Carlevaro, ; Wong et al., ). However, there are increasing concerns about shortages of nurses in many countries (Al‐Hamdan, Manojlovich, & Tanima, ; Labrague et al., ), including Nigeria (Salami, Dada, & Adelakun, ). With an increasing rate of turnover among nurses and general shortage of nurses, the attention of researchers has begun to shift from job satisfaction and commitment of nurses to career satisfaction and commitment.…”
mentioning
confidence: 99%